AB0533 Gender differences in spinal mobility reduction caused by ankylosing spondylitis in medium and long term assessed by a motion capture system. (23rd January 2014) - Collantes-Estevez, E.; Garrido-Castro, J. L.; Perez-Guijo, V.; Gonzalez-Navas, C.; Gil-Cabezas, J.; Garcia-Rodriguez, M. A.; Font-Ugalde, P.; Galisteo, A. M.; Medina-Carnicer, R.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease which causes a reduction in the patient mobility. Several studies show that, at radiological level, structural damage is much higher in men. There are few studies about gender differences in spinal mobility. Recently new technologies as motion capture have been introduced for assessing spinal mobility[1 ]. Objectives: To analyze, using measures obtained by a motion capture system, gender differences in spinal mobility of patients with AS in the medium and long term. Methods: 70 AS patients were analized (76.7% men). Two groups of patients were defined: medium and long term according disease duration (long term > 10 years). Cervical and spinal mobility were assessed using a motion capture system, the UCOTrack© [1]. Questionnaries about function and activity, conventional metrology (BASMI), and radiological scores (mSASSS) were also obtained. From motion capture several measurements were analyzed included a metrological index, the UCOASMI, based on motion capture measurements. Results: No significant differences between men and women in self-rated questionnaires were found, although women obtain worse scores particularly in the medium term. Occiput-wall distance differences was found between sexes. Some measures obtained by the motion capture system were different between genders: UCOASMI, lateral spinal flexion and cervical flexion. Conclusions: Results obtained by motion analysis corroborate similarities between genders as shown by several authors. Men have better mobility at medium term, inverting this difference at long term due mainly to structural damage. Motion capture provided additional accuracy information that can be useful in the diagnosis and therapeutic management of the disease. References: Assessment of spinal mobility in ankylosing spondylitis using a video-based motion capture system. Garrido-Castro J.L, Medina-Carnicer R, Schiottis R., Galisteo A.M, Collantes E., Gonzalez-Navas C. Manual Therapy 2012 Oct;17(5):422-6. Disclosure of Interest: None Declared